The PopHEAD study: a population-based, cross-sectional study on headache burden in Norway: methods and validation of questionnaire-based diagnoses - Maria Bengtson Argren; Helene Engstrand; Andreas Kattem Husøy; John-Anker Zwart; Bendik Slagsvold Winsvold (The Journal of Headache and Pain)
Abstract Background There is a lack of up-to-date information on the prevalence and burden of headache in Norway. Here we describe the methods and validation of the diagnostic tool of the PopHEAD study, a study designed to determine the prevalence and burden of migraine, tension-type headache, and medication-overuse headache. Method PopHEAD is a Norwegian population-based cross-sectional study conducted in Vestfold and Telemark County in 2023. A random sample of 28,753 individuals aged 18 to 70 was invited to participate. The study used a digital version of the Headache-Attributed Restriction, Disability, Social Handicap and Impaired Participation (HARDSHIP) questionnaire, translated into Norwegian using the Lifting The Burden translation protocol. A subsample of participants was contacted by telephone within four weeks for an interview with a headache neurologist blinded to the questionnaire responses. Headache disorders were diagnosed according to the criteria of the International Classification of Headache Disorders version 3. Validity was expressed by sensitivity, specificity and Cohen’s kappa (κ). Results In total, 8,265 (3,344 men and 4,921 women) responded. Most men (75.0%) and women (89.7%) reported having had a headache in the past year. Of 667 participants contacted for a telephone interview, 505 responded. The sensitivity and specificity of the questionnaire-based diagnoses were 97% and 72% for self-reported headache in the previous year (Cohen’s kappa κ = 0.72), 77% and 85% for migraine (κ = 0.61), 77% and 74% for tension-type headache (κ = 0.51), and 58% and 99% for medication-overuse headache (κ = 0.63), respectively. Conclusion The PopHEAD questionnaire is a valid tool for identifying individuals with lifetime headache, migraine, tension-type headache, and medication overuse headache.